UAV-assisted MEC systems: architecture, key technology, and future challenges - Tiankui ZHANG; Yu XU; Yuanwei LIU; Dingcheng YANG; Yuanhong REN (Dianxin kexue)
With the fast deployment of 5G and the on-going development of 6G, unmanned aerial vehicle (UAV)-assisted mobile edge computing (MEC) technology has significant advantages in the terms of overcoming the geographic restrictions, addressing the computational requirements of terminal devices, and enhancing the task offloading rate of the systems, which attracts wide attentions in academia and industry.The concept and the technique advantages of the UAV-assisted MEC systems were firstly clarified, and a general UAV-assisted MEC architecture was proposed, along with the definition of each function module.Then the classic application scenarios were summarized, and the existing key techniques were sorted out, based on which the design methods for the UAV-assisted MEC were achieved.Finally, the research directions and the potential challenges in the future were prospected and clarified.